Chromosome-scale genome assembly and gene annotation of the Alligator Gar (Atractosteus spatula) - Qing Wang; Qianqian Yu; Xiangqian Dong; Hengjin Chen; Xue Tian; Peng Qi; Haitao Wu; Yuxiang Yuan (Scientific Data)
Abstract Given the aggressive nature and robust survival capabilities of the alligator gar (Atractosteus spatula), if it was to exist in a new environment as an invasive species, it could cause significant disruption to the invaded ecosystem. Building on the continuity and completeness of the existing draft genome were not optimal, this study has updated a high-quality genome of the alligator gar at the chromosome level, which was assembled using Oxford Nanopore Technology and chromatin interaction mapping (Hi-C) sequencing techniques. In summary, the alligator gar genome in this study was 1.05 Gb in size with a contig N50 of 15.7 Mb and scaffold N50 of 56.8 Mb. We captured 98.26% of assembled bases in 28 pseudochromosomes. The completeness of the final chromosome-level genome reached 96.7%. Meanwhile, a total of 19,103 protein-coding genes were predicted, of which 99.83% could be predicted with functions. Taken together, the present high-quality alligator gar chromosome-level genome provides a valuable resource for exploring the underlying genomic basis to comprehend the functional genomics, chromosome evolution, and population management of this species.